Sosialisasi Cybersecurity Untuk Ibu-Ibu Di Sawah Lebar Baru Untuk Mencegah Cyber Crime - Miki Andika; Nurfitra Soleha Anisa; Astri Septiani; Wayan Merianti; Armansyah Dafa ’Ramadhan (Utami Publisher, 2026)
This paper summarizes the community service activity regarding the introduction of cybersecurity to mothers in RT 14, Sawah Lebar Baru. The rapid development of digital technology and social media has exposed housewives to various cyber crime risks. The aim of this activity is to increase the awareness and knowledge of the community on the importance of digital security and practical steps to avoid cyber threats. The research method used is socialization and practical training. The results indicate a significant increase in participants' knowledge and the successful application of security measures, confirmed through direct observation of the training process. It is concluded that continuous community education is essential in creating a safe digital environment. The program emphasized the importance of Two-Factor Authentication (2FA) and identifying hoax news.